Clinical Effects of Korean Red Ginseng in Postmenopausal Women With Hand Osteoarthritis: A Double-Blind, Randomized Controlled Trial - Kim, Hye In; Chon, Seung Joo; Seon, Ki Eun; Seo, Seok Kyo; Choi, Yun-Rak (Frontiers in Pharmacology, 2021)
Background Although many menopausal Asian women use herbal remedies for joint pain, there are no studies evaluating the efficacy of Korean red ginseng on osteoarthritis symptoms in postmenopausal women. The purpose of this study is to analyze antioxidant enzyme activity, oxidative stress markers, and pain scores before and after red ginseng consumption, to assess its effect in postmenopausal women. Methods This prospective, double-blind, randomized controlled trial enrolled 52 postmenopausal women who presented with hand edema and/or pain and were diagnosed as degenerative arthritis of the hand. Patients were randomly assigned to the red ginseng (RG) group (supplemented with 3 g/d of RG for 12 weeks) or the placebo group. Changes in pain and Disability of the Arm, Shoulder, and Hand (DASH) scores, antioxidant enzyme, oxidative stress markers, serum estradiol levels, and endometrial thickness were analyzed. Results The pain score and DASH score were significantly improved in the RG group (both p < 0.05). The improvement of pain score at rest, during work or sport, and DASH score was significant compared to that of the placebo group. The superoxide dismutase level increased (p < 0.05) and the malondialdehyde level decreased (p < 0.05) significantly in the RG group, while none of the antioxidative factors showed a significant change in the placebo group. Serum estradiol levels and endometrial thickness were not affected by RG supplementation. Conclusion RG may be an effective dietary supplement for postmenopausal women with degenerative osteoarthritis of the hand. It may relieve pain and improve antioxidative activity without the risk of endometrial thickening.